Late Quaternary high uplift rates in northeastern Sicily : evidence from calcareous nannofossils and benthic and planktonic foraminifera - E. Di Stefano; M. Agate; A. Incarbona; R. Sprovieri; S. Bonomo; F. Russo (Facies, 2012)
The northeastern part of Sicily is characterized by intense seismic activity. Several systems of faults have been recognized in Pliocene and Pleistocene sediments in the area and, in fact, estimates of uplift rates are among the highest recorded in Sicily and south Italy. We examined calcareous nannofossil and benthic and planktonic foraminifera assemblages from pelitic sediments of the Contrada Zura section (Barcellona Pozzo di Gotto Basin, Furnari village, Messina). The occurrence of Emiliania huxleyi, a coccolithophore species which appeared in the oceanic record about 270,000 years ago, is witness to the uniqueness of this outcrop, while the planktonic/benthic foraminifera ratio indicates a deep (slope) environment, in agreement with previous observations on macrobenthic and ostracod paleo-communities. Independently from the numerical estimate of the paleo-depth, there is little doubt that the occurrence of E. huxleyi in such sediments might be explained by exceptional uplift rates. Since resulting uplift rate estimates, between 3.2 and 5.5 mm/year, exceeded by far the regional, longer-term, vertical tectonic motion, we argue that a major contribution of coseismic displacement along active faults occurred in the Furnari area.